2018
DOI: 10.1038/s41467-018-06648-6
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility of the circadian protein BMAL1 and HNF4α in hepatocellular carcinoma

Abstract: Hepatocyte nuclear factor 4 alpha (HNF4α) is a master regulator of liver-specific gene expression with potent tumor suppressor activity, yet many liver tumors express HNF4α. This study reveals that P1-HNF4α, the predominant isoform expressed in the adult liver, inhibits expression of tumor promoting genes in a circadian manner. In contrast, an additional isoform of HNF4α, driven by an alternative promoter (P2-HNF4α), is induced in HNF4α-positive human hepatocellular carcinoma (HCC). P2-HNF4α represses the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 70 publications
(75 reference statements)
7
124
0
Order By: Relevance
“…Chronic jet lag caused disruption of hepatic cholesterol, bile acid, and xenobiotic metabolism via elevation of constitutive androstane receptor (CAR), which is a regulator of xenobiotic metabolism and associated with hepatocarcinogenesis, indicating the association of circadian rhythms with liver metabolism and HCC development . Another study has found negative correlation of expression levels between BMAL1 and HNF4α, which is important for hepatocyte fate determination and functions . HNF4α had circadian activities with rhythmic expression of downstream targets such as cyclin B1 and D1 in murine hepatocyte line AML12 cells .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic jet lag caused disruption of hepatic cholesterol, bile acid, and xenobiotic metabolism via elevation of constitutive androstane receptor (CAR), which is a regulator of xenobiotic metabolism and associated with hepatocarcinogenesis, indicating the association of circadian rhythms with liver metabolism and HCC development . Another study has found negative correlation of expression levels between BMAL1 and HNF4α, which is important for hepatocyte fate determination and functions . HNF4α had circadian activities with rhythmic expression of downstream targets such as cyclin B1 and D1 in murine hepatocyte line AML12 cells .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…Another study has found negative correlation of expression levels between BMAL1 and HNF4α, which is important for hepatocyte fate determination and functions . HNF4α had circadian activities with rhythmic expression of downstream targets such as cyclin B1 and D1 in murine hepatocyte line AML12 cells . Human HCC lines, HepG2, Hep3B, and Huh7 cells, expressed high levels of HNF4α and low levels of BMAL1, and overexpression of BMAL1 in HepG2 cells caused elevated apoptosis and decreased tumor growth in xenograft mouse models, indicating the roles of circadian rhythms in hepatocyte carcinogenesis …”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…Even though the full compendium of TFs involved in promoting these enhancer landscape changes have not been fully characterized yet, HNF4A binding sites are highly enriched near genes downregulated in hepatocellular carcinomas (Ramaker et al, ), in line with work implicating this core hepatic TF in tumour suppression (Fekry et al, ; B.‐F. Ning et al, ; Yin et al, ).…”
Section: Nafld‐associated Remodeling Of Liver Gene Regulatory Landscapesmentioning
confidence: 86%
“…Forced re‐expression of HNF4A in a rat model of hepatic failure induced expression of other hepatic TFs and reversed fatal liver failure by restoring hepatocyte function (Nishikawa et al, ). Moreover, several studies indicate the tumor suppressor role of HNF4A in hepatocellular carcinomas (Yin et al, ; Fekry et al, ; B.‐F. Ning et al, ).…”
Section: Liver Cis‐regulatory Networkmentioning
confidence: 99%
“…Among those downregulated genes in sh-LINP1 cells, HNF4α, which has been reported to affect cell proliferation in several cancers, [12][13][14][15] was significantly overexpressed in AML patients while downregulated in CR patients ( Figure 2D). Therefore, HNF4α expression was positively correlated with LINP1 ( Figure 2E).…”
Section: Linp1 Regulated Hnf4α Signaling To Promote Aml Cell Survivalmentioning
confidence: 95%